2020
DOI: 10.1093/nar/gkaa906
|View full text |Cite|
|
Sign up to set email alerts
|

TriTag: an integrative tool to correlate chromatin dynamics and gene expression in living cells

Abstract: A wealth of single-cell imaging studies have contributed novel insights into chromatin organization and gene regulation. However, a comprehensive understanding of spatiotemporal gene regulation requires developing tools to combine multiple monitoring systems in a single study. Here, we report a versatile tag, termed TriTag, which integrates the functional capabilities of CRISPR-Tag (DNA labeling), MS2 aptamer (RNA imaging) and fluorescent protein (protein tracking). Using this tag, we correlate changes in chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 68 publications
2
11
0
Order By: Relevance
“…Next, to monitor the activation of an endogenous promoter, we inserted TriTag into the C-terminus of human H2B via CRISPR/Cas9-mediated homologous recombination in HeLa cells which stably expressed stdMCP-tdTomato. Consistent with our previous finding 39 , the transcription of H2B loci occurred in discontinuous bursts (Fig. 1b and Supplementary Video 3 ).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Next, to monitor the activation of an endogenous promoter, we inserted TriTag into the C-terminus of human H2B via CRISPR/Cas9-mediated homologous recombination in HeLa cells which stably expressed stdMCP-tdTomato. Consistent with our previous finding 39 , the transcription of H2B loci occurred in discontinuous bursts (Fig. 1b and Supplementary Video 3 ).…”
Section: Resultssupporting
confidence: 92%
“…Real-time imaging revealed that nascent RNAs were produced in bursts (Supplementary Fig. 2a, b ), which is consistent with previous studies 39 , 45 , 46 . To monitor Narta activation, Dox was added to induce stdMCP-PH expression for 12 h and then real-time imaging was recorded for 2 h. Quantitative analysis indicated that the addition of Dox induced more de novo RNA production (~6-fold) which was defined by the total intensity of individual stdMCP-tdTomato spots (Supplementary Fig.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…dCas9, foldon-GFP-PCP, and stdMCP-tdTomato lentivirus were prepared as previously described. 33 , 34 U2OS cells were infected with dCas9 lentivirus and selected with blasticidin to obtain a dCas9 stable cell line. The dCas9-U2OS cells were sequentially infected with foldon-GFP-PCP lentivirus and stdMCP-tdTomato lentivirus and selected by fluorescence-activated cell sorting (FACS) (Sony, MA900) to generate the dCas9-U2OS/foldon-GFP-PCP and dCas9-U2OS/stdMCP-tdTomato cell lines.…”
Section: Methodsmentioning
confidence: 99%
“…Instantaneous detection of nascent mRNA molecules by this method has enabled studies of transcription dynamics in living cells from bacteria to humans [19][20][21][22][23]. Very recent approaches combine in vivo labeling of DNA, nascent RNA, and a fluorescent protein to resolve the spatiotemporal process of transcriptional induction at a single locus [24]. Although these approaches are highly sensitive and are applicable at single-cell resolution, they require engineered genes for visualization and are generally time-consuming, which greatly limits the parallel study of several genes or their application to diverse conditions that modulate transcriptional dynamics.…”
Section: Technical Approaches To Capture Gene Expression In Vivomentioning
confidence: 99%